Evaluación de la actividad antimicrobiana y antimicótica de tres extractos de la raíz de Hippobroma longiflora (L) G. Don (Cholo valiente), por el método de difusión en agar. - Castillo Rojas, Jhon Fernando (2013)
This research "Evaluation of the antimicrobial and antifungal activity of three extracts from the root of Hippobroma longiflora (L.) G. Don (brave Cholo) by the agar diffusion method " was performed at the Laboratory of Microbiology of Phytochemistry and Chemical Analysis Center of the National University of Loja. The plant species Hippobroma longiflora (L.) G. Don (brave Cholo) was collected on the lemons, Canton Province of Zamora Zamora Chinchipe, a place where the leaves of the plant species mentioned for the treatment of wounds caused by Leishmania spp Parish used . The fundamental objective of the research was to evaluate the antibacterial and antifungal activity of root Hippobroma longiflora , for which the hexane , ethanolic and aqueous extracts were obtained part mentioned , preparing dilutions of 1 /100, 1/1000th 1:10,000 using the hexane solvent , ethanol and water for each extract . Dilutions were impregnated paper discs Whatman No3 with 20ul, which were placed on media plates Muller Hinton previously inoculated with the strains ATCC Escherichia coli ( 25922) , Staphylococcus aureus ( 25923 ) , Klebsiella pneumoniae ( 13883 ) , Pseudomonas aeruginosa ( 27853 ) , and Candida albicans ( 26790 ), together with discs for positive and negative controls. Diffusion method was used in agar disk so after 24 hours of incubation proceeded to the reading of the zones of inhibition . It was concluded in this study that the hexane , ethanolic and aqueous extracts of the root of Hippobroma longiflora in dilutions of 1 /100, 1/1000th 1:10,000 not show inhibition of growth of ATCC strains tested using the agar diffusion method with disk. Keywords: Hippobroma longiflora, agar diffusion method with disco, antibacterial and antifungal activity.